Morphology of Hoof in Buffaloes and its Implications for Designing of Boots to Protect the Hoof - Dhoolappa, M. (Indian Journal of Veterinary Anatomy, 2018)
The hoof of animal is considered as the most important organ for supporting weight and for movement. There are considerable variations in its shape, size, and histology in different species of animals. The objective of the study is to understand the morphology and morphometry of the hoof in buffaloes, which will be used as baseline data for designing affordable and durable hoof-boots for dairy buffaloes in future. The buffalo hoof consisted of first phalanx, half of the second phalanx, digital cushion, joint, ligaments and tendons and covered by a horny capsule (epidermis). The measurements of the hoof (n=14) were carried out on adult crossbred buffaloes regardless of the age and species. The  hickness of the capsule in dairy buffaloes was assessed. Based on the size-range data obtained, hoof boots of different sizes (small, medium and large) will be designed by using waste materials with the aim of withstanding a total weight to the tune of 300-500 Kgs in dairy buffaloes.